The Role of Digital Transformation and Incoterm Selection in Enhancing Competitive Advantage: Evidence from Indonesian Freight Forwarders - Sugiono, Ahmad; Rahayu, Agus; Wibowo, Lili Adi; Hurriyati , Ratih (Jurnal Locus Penelitian dan Pengabdian, 2025)
The research investigates the influence of digital transformation and the choice of Incoterms on the competitive positioning of freight forwarding firms. Although previous studies have explored digitalization and trade terms individually, limited attention has been given to their joint effects within emerging market contexts. Data were collected from 130 freight forwarding companies in Indonesia through a structured questionnaire. Three indicators measured digital transformation (e-documentation, real-time tracking, system integration), four indicators captured Incoterm selection (risk management, cost control, delivery responsibility, flexibility), and five indicators assessed competitive advantage (cost efficiency, reliability, Speed, flexibility, innovation). Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to test the hypotheses. The results reveal that both digital transformation and the selection of Incoterms significantly enhance competitive advantage. Digital tools strengthen service reliability and operational efficiency, while strategic Incoterm choices improve risk sharing, cost control, and customer responsiveness. Freight forwarders should integrate digital technologies and adopt flexible Incoterm strategies to sustain competitiveness in dynamic logistics environments. This study is among the first to integrate technological and contractual perspectives, providing novel evidence on how digital transformation and Incoterm selection jointly shape competitive advantage in the freight forwarding sector of a developing country.